Attitudes of People towards Facebook Advertising of Controvercial Products A Comparison of Different Ethnic Groups in Sri Lanka - Lakshika, P.; Samarasinghe, R. (Sabaragamuwa University, 2017)
Understanding customer's attitudes toward advertising has been one of the purposes of advertisers. Advertisements that are effective in conveying its messages to audiences can promote and construct mindfulness on the organization's offerings. The purpose of this research is to determine the attitudes towards advertising of certain controversial products on Facebook in the western province of Sri Lanka. Three ethnic groups (Sinhala, Tamil, and Muslim) were selected and three controversial products were used in the study. The attitudes are measured in terms of advertising likability and dislikability to determine the overall level oflikable and dislikable attitude towards Facebook advertising of controversial products. The research focus on two objectives; to measure the level of attitude with regard to controversial products advertising on television among different ethnic groups and to identify if different ethnic groups hold different viewpoints regarding advertising of such controversial products. A model was developed to measure the level of attitude by using advertising likability and dislikability indicators with the use of randomly selected controversial products, specifically Female Hygiene, Female Underwear and Political advertisement. A sample of 384 respondents was used to collect information and quota sampling method was used. Based on the results, it was identified that ad likability is shown for female hygiene product advertisements and ad dislikability shown for political advertisements and female
Keywords: Attitudes of People, Advertising, Facebook, Controversial product, Ethnic groups